The Safety And Efficacy of Implanon Implant in A Sample of Iraqi Women: A Cohort Study - Samah Radhi Lateef 1, Makkiyah Radhi Lateef 2, Qatarulnada Khudhair Abbas3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim of the study: we planned and conducted the current cohort study to evaluate the safety and efficacy of this new contraceptive method in a sample of Iraqi women.Patients and Method: This cohort study was carried out at some governmental health institutes such as Al-Diwaniyah Maternity and Child Teaching hospital and Al-Shamiyah teaching hospital and some private clinics. The beginning of the study is dated back to the 2nd of January 2016; the study continued till end of June 2019 and included 53 women. Inclusion criteria included any women with implanon implant that was recently impanted. The variables to be evaluated included age, residency, gravidity, parity and abortions in addition to principal outcomes, complications (amenorrhea, bleeding and development of ovarian cysts) and pregnancy six months following removal of the implant. All women participating in the current study were followed up till at least six months after implant removal.Results: The outcome of implanon use was assessed following a period of follow up that ranged from 2 to 3 years with a mean of 2.89 years, as shown in table 2. Contraceptive failure was no seen in any case with a failure rate of 0.0 %. Amenorrhea was the most frequent side effect and it has been seen 18 (34.0 %). Ovarian cyst was seen in 6 cases accounting for (11.3 %) and bleeding was seen in 2 cases only accounting for (3.8 %). Complications, amenorrhea, ovarian cysts and bleeding were not significantly correlated to any of demographic or obstetric characteristics of the study group (P > 0.05.